THE CLASSIFICATION AND CONTROL OR NAVY EXPENDITURES. - Pierpont, W. K. (The Accounting Review, 1946)
The article describes the detailed accounting procedures particularly those in effect in classifying and controlling expenditures in the U.S. Navy Department in general and the Navy Bureau of Ordnance in particular, as of January 1946. During the last two years, the Navy Department has been studying various phases of its accounting procedures with the intention of revising these procedures wherever it seemed appropriate. As a result of this study certain revisions in accounting for the expenditures of the Navy Department were placed in effect as of July 1945. No attempt will be made in this article to compare to any extent the old and the new procedures for expenditure accounting, but the procedures in effect since July 1945, will be described. The author informs that the expenditures of a federal department are subject to various controls outside the department itself. Such controls include those over the accounting classifications used to report money expended, as well as the usual control over the amount of money expended. Exclusive of the General Accounting Office, which is essentially an organization to audit expenditures of the U.S. government, the principal extra-agency controls for expenditures of the Navy Department arise from the U.S. Congress and from the U.S. Bureau of the Budget.